Analisa Jaringan Kerja dengan Metode CPM pada Proyek Pembangunan Gedung Balai Diklat BPK RI Perwakilan Provinsi Sumatera Utara di Medan - Hermanto, Hermanto; Mustafa, Kamil; Banjarnahor, Banjarnahor (JOURNAL OF INDUSTRIAL AND MANUFACTURE ENGINEERING, 2018)
Research was conducted at the training center bulding projec RI BPK Representative in Medan, North Sumatera, where the purpose of this research is to create a complex framework of activities based on project completion time and human resources available for job creation building structures manager. The framewwork presented in the form of work flow diagram (Network Diagram). From the data obtainned by the completion of the project structure has been estimated tim required to finish the job thus structure with the critical path method (Critical Path Method – CPM). After the calculation of forward and backward calculation is obtained : fastest tim starting and completion activities, no later than beginning and completion of, the lenght of the interval delay /postponement of activities. With the CPM method, completion building structure mnagement training center of RI BPK representative of North Sumatera Province is known than the sum of time critical activities. These critical activities each time interval did not have to delay the implementation of activities. The activities that are on the critical path is the activity with the notation : A-C-E-F-I-L-MQ-U-V-W-X-Y-Z-AA-AC-AD gained 4+9+6+6+1+3+6+1+1+6+1+6+6+1+6+1 = 64 days.